The Causes of Student Dropout from Dual Vocational Education (DVE): An Empirical Study in Thailand - Tungkunanan, Pariyaporn (Journal of Technical Education and Training, 2020)
In Thailand, focus on the dual vocational education (DVE) program is an important policy that the government encourages in parallel with driving national development, according to the principles of Thailand 4.0. However, the dropping out of DVE students is still ongoing. The government and the industrial and service sectors will, therefore, suffer economic loss through waste of investment in education coupled with economic loss to the country in various ways. Therefore, this study aimed to find the causes of student dropout from DVE programs in Thailand by using qualitative method research with in-depth interviews with 40 key informants, covering four regions of Thailand, who are stakeholders in the DVE system. The data were analysed thematically by the three-step research process for qualitative lesson research. The research results show that the causes of student dropout from DVE programs are mainly because DVE students of certificate level, age between 16-18 years old, have low maturity in the control of emotions, adaptation to society, and making rational decisions to solve problems, followed by establishments in Thailand not yet understanding the patterns, procedures, or processes of DVE as they should; the third cause is family, because student family conditions may affect the mind and concentration of the student, and the last one are vocational training schools, who may have policies, systems, regulations, and guidelines for managing DVE that are unclear or not as conducive to success for DVE students. Therefore, teachers, establishments, students, and parents should bring research results to create a system for the screening, preventing, and solving problems of student dropout from DVE programs and reducing the waste of investment in education by the state and economic losses to the country.